2012
DOI: 10.1111/hdi.12000
|View full text |Cite
|
Sign up to set email alerts
|

Primary brachial vein transposition for hemodialysis access: Report of a case and review of the literature

Abstract: The superiority of autogenous fistulae in patients with end-stage renal disease, performing hemodialysis, is well established and largely accepted. However, in case that superficial veins in the upper arm are not available for fistula construction, brachial vein transposition may be a viable alternative prior to graft placement. This transposition could be done as a primary or staged procedure, depending on the vein size. We present the case of a 63-year-old male patient with a thrombosed arteriovenous graft i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Medical therapy is also used for TC patients, especially for UTC patients using aggressive phosphate binders, calcimimetics, using low-calcium dialysate solutions, and increased length and frequency of hemodialysis treatments [ 28 ]. Fatehi et al [ 8 ] reported a case that keeping on hemodialysis improved the symptoms and reduced the mass of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapy is also used for TC patients, especially for UTC patients using aggressive phosphate binders, calcimimetics, using low-calcium dialysate solutions, and increased length and frequency of hemodialysis treatments [ 28 ]. Fatehi et al [ 8 ] reported a case that keeping on hemodialysis improved the symptoms and reduced the mass of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Since that first described experience of a brachial artery-brachial vein arteriovenous fistula (BVAVF), a number of studies have demonstrated varied results for its rates of patency and complications. [11][12][13][14][15][16][17][18] Few studies have compared the BVAVF directly with the AVG.…”
mentioning
confidence: 99%